1998
DOI: 10.1152/ajpcell.1998.274.1.c129
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fos andjun genes in human skeletal muscle after exercise

Abstract: It is believed that the induction of the fos and jun gene family of transcription factors might be at the origin of genetic events leading to the differential regulation of muscle-specific genes. We have investigated the effect of a 30-min running bout in untrained subjects on the expression of the mRNAs of all members of the fos and jun gene families, including c- fos, fosB, fosBdel, fra-1, and fra-2 as well as c- jun, junB, and junD. While the fos family members were transiently upregulated 10- to 20-fold (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 28 publications
6
77
0
Order By: Relevance
“…Hypoxia induces transcriptional activation of the canonical AP-1 components c-Fos and c-Jun in vitro (24), as does experimental cerebral ischemia (25) and ischemia in human brain tissue (26). Nonischemic stimuli can trigger AP-1 transcription factor expression, e.g., moderate exercise in human skeletal muscle increases c-Fos, c-Jun, Fra-1, and JunB (27). Similarly, the increased occupancy of the RE-1 site by p53 in ischemic muscle (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia induces transcriptional activation of the canonical AP-1 components c-Fos and c-Jun in vitro (24), as does experimental cerebral ischemia (25) and ischemia in human brain tissue (26). Nonischemic stimuli can trigger AP-1 transcription factor expression, e.g., moderate exercise in human skeletal muscle increases c-Fos, c-Jun, Fra-1, and JunB (27). Similarly, the increased occupancy of the RE-1 site by p53 in ischemic muscle (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The early cellular signals that are associated with contractile activity are known to induce the subsequent expression of mRNAs encoding transcription factors that regulate changes in skeletal muscle phenotype Puntschart et al, 1998). Several studies have demonstrated that changes in the mRNA expression of transcription factors precede the contractile activity-induced regulation of mitochondrial and metabolic plasticity in skeletal muscle (Connor et al, 2001;Irrcher et al, 2003;Michel et al, 1994;Pilegaard et al, 2003;Xia et al, 1997).…”
Section: Gene Expression Response To Contractile Activity and Recoverymentioning
confidence: 99%
“…Several studies have demonstrated that changes in the mRNA expression of transcription factors precede the contractile activity-induced regulation of mitochondrial and metabolic plasticity in skeletal muscle (Connor et al, 2001;Irrcher et al, 2003;Michel et al, 1994;Pilegaard et al, 2003;Xia et al, 1997). These include the induction of a family of immediate early genes (c-fos, c-jun), the early growth response gene-1 (Egr-1), specificity protein 1 (Sp1) and nuclear respiratory factor-1 (NRF-1), which respond to both acute and chronic contractile activity (Abu-Shakra et al, 1993;Connor et al, 2001;Irrcher and Hood, 2004;Michel et al, 1994;Murakami et al, 1998;Neufer et al, 1998;Puntschart et al, 1998;Takahashi et al, 1993). Egr-1 and Sp1 are known to be involved in regulating the transcription of cytochrome c, a nuclear-encoded protein of the electron transport chain (Connor et al, 2001;Freyssenet et al, 2004), while NRF-1 is involved in the transcriptional activation of an even greater diversity of nuclear genes encoding mitochondrial proteins (Kelly and Scarpulla, 2004), including the newly discovered mtDNA transcription factors TFB1M and TFB2M (Gleyzer et al, 2005).…”
Section: Gene Expression Response To Contractile Activity and Recoverymentioning
confidence: 99%
“…The activation of key kinases and mediators within these pathways-importantly, but not exclusively, AMP-activated protein kinase [1,2], Ca 2+ / calmodulin-dependent kinases [3], atypical protein kinase C [4,5], and mitogen-activated protein kinase (MAPK) [6]initiates the upregulation of glucose uptake, which is the acute metabolic effect, and also regulates the adaptive response of the muscle to exercise training. Several of these pathways are involved in the exercise-dependent activation of the transcriptional co-activator peroxisome proliferatoractivated receptor-γ coactivator-1α (PGC-1α) [7,8] and induction of transcription factors nuclear factor-κ light chain gene enhancer in B cells [9], FBJ osteosarcoma oncogene (c-FOS) and the jun oncogene (c-JUN) [10] in the working muscle. The exercise-dependent differential gene expression in the muscle is an important mechanism in the adaptation to regular physical activity.…”
Section: Introductionmentioning
confidence: 99%